Motivation of self-gift consumption in fashion goods - Du, Shengye (2019)
This study aims to determine the most important motivations for self-gifting in a particular context of fashion goods. Through the statistical analysis of the data obtained from online surveys, the self-gifting motivation was studied in a quantitative way.